Inhibition of CEBPB Attenuates Lupus Nephritis via Regulating Pim-1 Signaling - Xiaoyang Wang; Weili Cheng; Xiaopan Chen; Yanan Gong; Guangjie Wang; Xiaoxue Zhang; Yuanyuan Qi (Mediators of Inflammation)
Systemic lupus erythematosus (SLE) is an autoimmune disease leading to inflammatory damage in multiple target organs, and lupus nephritis (LN) is one of the most life-threatening organ manifestations. CCAAT/enhancer-binding protein β (CEBPB) regulates the NLRP3 inflammasome and is involved in the pathogenesis of SLE. However, the role and mechanism of CEBPB in LN remains unclear. MRL/lpr mice and lipopolysaccharides (LPS) combined with adenosine triphosphate- (ATP-) treated glomerular podocytes were used as models of LN in vivo and in vitro, respectively. In vivo, we investigated the expressions of CEBPB during the development of MRL/lpr mice. Then we assessed the effect of CEBPB inhibition on renal structure and function through injecting shCEBPB lentivirus into MRL/lpr mice. In vitro, glomerular podocytes were treated with Pim-1-OE and siCEBPB to explore the relation between CEBPB and Pim-1. The progression of LN in mice was associated with the increased level of CEBPB, and the inhibition of CEBPB ameliorated renal structure impairments and improved renal function damage associated with LN. Knockdown of CEBPB could suppress the activation of NLRP3 inflammasome and the secretion of IL-1β and IL-6. Furthermore, the knockdown of CEBPB could inhibit NLRP3 inflammasome activation and pyroptosis via binding to Pim-1 promoter to downregulate its expression, and the overexpression of Pim-1 reversed the effects of CEBPB deficiency. The regulation of CEBPB on Pim-1 facilitated pyroptosis by activating NLRP3 inflammasome, thereby promoting the development of LN.